Polyarteritis nodosa presenting as a pyrexia of unknown origin. Issue 925 (1st November 2002) - Henderson, J; Cohen, J; Jackson, J; Wiselka, M
Abstract : A case of an 18 year old woman is reported who presented with a pyrexia of unknown origin having returned from a trip to India. She initially had constitutional symptoms only, which rapidly progressed to a multisystem disorder. The difficulty in making the diagnosis of polyarteritis nodosa, especially with the possible differential diagnosis of infection after her recent travel, is discussed. The discussion reviews the condition of polyarteritis nodosa and analyses the diagnostic difficulties in this case.